Aircraft wake vortices characterization and alleviation - El-Sayed, Omer Ali (Kulliyyah of Engineering, International Islamic University Malaysia, 2010)
The serious impact of the trailing vortices from large aircraft is well known. Many examples exist of the damage caused to following aircraft caught up in the swirling wake shed from an upstream aircraft. Motivation behind the present investigation is the alleviation of the rolling moment induced on the following aircraft by means of a differential spoiler setting DSS's. An experimental investigation on a wing tip vortex generated by generic aircraft model, Subsonic Wall Interference Model (SWIM) in plain and flapped wing configurations was conducted in a low speed wind tunnel at Korean Aerospace Research Institute (KARI). Particle image velocimetry was used to characterize wing tip vortex structures as well as to distinguish and quantify vortex meandering and further remove its effects. In subsequent experiments investigation on wake vortices has been carried out in the international Islamic University Malaysia (IIUM) low speed wind tunnel for the evaluation of differential spoiler settings (DSS) capabilities in modifying the span-wise wing load and further reduces the wake vortex hazard. Advanced PIV technique was used to measure the wake velocities at four cross-section planes down-stream of the aircraft half model in the near and extended near wake field. Model was investigated at high lift configuration as well as at four DSS configurations believed to modify the span-wise wing loading (two inboard and two outboard loading cases). Results reveal a noticeable inboard shift of wing loading along with the direct interaction of the spoiler's wake and flap tip vortex for the inboard loading cases. Implementation of DSS results in a substantial redistribution of the flap tip vortex circulation with a diameter of the merged vortex increased by a factor of up to 2.72 times, relative to the undisturbed flap tip vortex. Inspection of the cross-stream distribution of axial vorticity shows up to 2.33 times reduction in the peak vorticity value. A 44% decrease of the maximum cross-flow velocity was recorded for the case of deployed spoilers relative to undisturbed flap tip vortex maximum cross-flow velocity. The wing tip vortex experiences the effect of wing load modification but doesn't show appreciable difference, both in terms of cross-flow velocity and local circulation distribution. Evaluations of the outboard loading results indicate a limited diffusion experienced by the vortex due to the increased level of turbulence. Influence of DSS's on the wake vortex structure emphasizes that separation distance (spoiler wake/wing-flap tips vortices) plays an important role in the favorable interaction expected. Finally assessment of the DSS's capabilities as a wake vortex attenuation device reveals, while position of the maximum induced rolling moments in the flap tip area is little influenced by the DSS's, the maximum induced rolling moment coefficient was reduced to a nearly one third relative to the undisturbed flap tip vortex value.